The expanding clinical spectrum of autoinflammatory diseases with NOD2 variants: a case series and literature review - Karamanakos, Anastasios; Vougiouka, Olga; Sapountzi, Evdoxia; Venetsanopoulou, Aliki I.; Tektonidou, Maria G.; Germenis, Anastasios E.; Sfikakis, Petros P.; Laskari, Katerina (Frontiers in Immunology, 2024)
Objective To assess the impact conferred by NOD2 variants on the clinical spectrum of patients with systemic autoinflammatory diseases (SAIDs) in Greece. Methods Consecutive patients (n=167) with confirmed SAIDs who underwent screening by next generation sequencing (NGS) targeting 26 SAID-associated genes, and carried at least one NOD2 gene variant, were retrospectively studied. The demographic, clinical and laboratory parameters were recorded. Results In total, 24 rare NOD2 variants in 23/167 patients (14%) were detected. Notably, 18 patients had at least one co-existing variant in 13 genes other than NOD2. Nine patients had juvenile- and 14 adult-onset disease. All patients presented with symptoms potentially induced by the NOD2 variants. In particular, the candidate clinical diagnosis was Yao syndrome (YAOS) in 12 patients (7% of the whole SAID cohort). The clinical spectrum of patients with YAOS (mean episode duration 8 days) was fever (n=12/12), articular symptoms (n=8), gastrointestinal symptoms (n=7; abdominal pain/bloating in 7; diarrhea in 4; oral ulcers in 3), serositis (n=7), and rash (n=5), while the inflammatory markers were elevated in all but one patient. Most of these patients showed a poor response to nonsteroidal anti-inflammatory drugs (n=7/9), colchicine (n=6/8) and/or anti-TNF treatment (n=3/4), while a complete response was observed in 6/10 patients receiving steroids and 3/5 on anti-IL1 treatment. Another 8 patients were diagnosed with either FMF (n=6) or PFAPA syndrome (n=2) presenting with prominent diarrhea (n=7), oral ulcers (n=2), periorbital swelling and sicca-like symptoms (n=1), or maculopapular rash (n=1). One patient had a clinically undefined SAID, albeit characterized by oral ulcers and diarrhea. Finally, one patient presented with chronic relapsing urticaria with periorbital edema and inflammatory markers, and another one had a Crohn-like syndrome with good response to anti-IL-1 but refractory to anti-TNF treatment. Conclusion NOD2 variants were detected in 1 out of 7 SAID patients and seem to have an impact on disease phenotype and treatment response. Further studies should validate combined molecular and clinical data to better understand these distinct nosological entities.